A Colocalized Scheme for Three-Temperature Grey Diffusion Radiation Hydrodynamics (Communications in Computational Physics, 2021)
A positivity-preserving, conservative and entropic numerical scheme is presented for the three-temperature grey diffusion radiation hydrodynamics model. Moreprecisely, the dissipation matrices of the colocalized semi-Lagrangian scheme are defined in order to enforce the entropy production on each species (electron or ion) proportionally to its mass as prescribed in [34]. A reformulation of the model is then considered to enable the derivation of a robust convex combination based scheme. Thisyields the positivity-preserving property at each sub-iteration of the algorithm whilethe total energy conservation is reached at convergence. Numerous pure hydrodynamics and radiation hydrodynamics test cases are carried out to assess the accuracy of themethod. The question of the stability of the scheme is also addressed. It is observedthat the present numerical method is particularly robust.
Keywords: Colocalized Lagrangian scheme; radiation hydrodynamics; grey diffusion; discrete entropy production; plasma physics simulations.